Physicians' Counseling on Toxoplasma gondii Prepregnancy Screening Tests: A Simulation-Based Study. Issue 6 (November 2020) - Sanei, Zahra; Sheybani, Fereshte; Eslami, Saeid; Naderi, HamidReza; Taherzadeh, Zhila; Vatanchi, Atiyeh Mohammadzadeh; Varzandeh, Marjan
Abstract : Objective: The aim of the study was to evaluate the ability of obstetrics and gynecologists about interpretation and counseling regarding Toxoplasma gondii prepregnancy screening tests. Methods: This research was a simulation-based study that was conducted using simulated patients from April 2018 to March 2019 in Mashhad, Iran. Cluster sampling of practicing obstetricians and gynecologists (OBGYNs) was performed by municipal districts. In this study, 2 scenarios were constructed to address the approach to a T. gondii seronegative (both IgG and IgM were negative) and seropositive (IgG was positive, and IgM was negative) women who are planning to become pregnant in scenario 1 and scenario 2, respectively. Results: With regard to scenario 1, T. gondii serological tests in seronegative individuals were correctly interpreted by approximately 90% of OBGYNs. However, in less than 10% of cases, counseling regarding Toxoplasma infection prevention was performed, most of which were not performed appropriately. With regard to scenario 2, the interpretation of test results was performed correctly by 80% of OBGYNs of whom almost 80% followed by appropriate counseling. Except for the relationship between T. gondii infection and cats as well as risk of abortion, level of physicians' knowledge regarding toxoplasmosis was estimated to be inadequate. Conclusions: Although it has been shown that physicians play an important role in raising awareness of toxoplasma-seronegative pregnant women about appropriate preventive measures, according to the results of our study, most T. gondii seronegative women who plan to become pregnant do not receive any consultation about the importance of following preventive measures, and in a minority of them, only avoidance of cat exposure is emphasized. Insufficient knowledge of providers was identified regarding immunopathogenesis of toxoplasmosis, preventive measures, interpretation of T. gondii serological test results, and optimal approach to the T. gondii prepregnancy serological test results that emphasizes on the importance of more effective education in these areas of knowledge and practice.